High proximal migration rate of a partially covered “big cup” duodenal stent in patients with malignant gastric outlet obstruction - van den Berg, Maarten W.; Walter, Daisy; Vleggaar, Frank P.; Siersema, Peter D.; Fockens, Paul; van Hooft, Jeanin E. (Endoscopy, 2014)
Endoscopic placement of self-expandable metal stents (SEMS) has emerged as a palliative treatment for patients with malignant gastric outlet obstruction (GOO). Recently, a new partially covered “big cup” SEMS has been developed to prevent both stent migration and tissue ingrowth. The aim of the study was to evaluate safety and efficacy of this SEMS in a cohort of patients with incurable malignant GOO. The study was terminated prematurely due to three proximal stent migrations in six patients. Migrations occurred at 2, 4, and 29 days, respectively, and necessitated endoscopic removal and placement of another SEMS. The remaining three patients had a patent SEMS at the end of follow-up. The high proximal migration rate of this new SEMS should be taken into account when considering routine clinical use in malignant GOO. Further research is warranted in order to find an optimal stent design that prevents both stent migration and tumor ingrowth.